A responsabilidade das empresas transnacionais na preservação dos direitos indígenas - Alves, Alessandra Vanessa (2024)
The present study aimed to identify the duties – expressed and implicit – that arise for transnational companies when their economic activities are conducted on indigenous lands or have an impact on them. To this end, identified the most recurrent violations of indigenous peoples' interests regarding the commercial exploitation of their lands or surroundings. Adopting the context of the Krenak people, it was identified that the Krenak, similar to other indigenous peoples, have experienced conflicts on multiple fronts due to large scale projects affecting their territoriality, access to natural resources (with prejudice to their subsistence), and their very way of life and existence. Reflecting on the commitment made to by political entities and their respective branches with the enactment of the Federal Constitution of 1988, the constitutional provisions were interpreted from a historical perspective. It was identified that economic exploitation of indigenous lands -contingent upon legislation - shall, if enacted (because it is not a constitutional duty but a mere possibility), adhere to the criteria previously outlined in the Constitution, including consultation with the peoples concerned, authorization by the National Congress, and the right to participate in the results of the extraction. Furthermore, the principles derived from these criteria include the exceptional nature of exploration, preservation of indigenous wealth - both material and immaterial - and recognition of indigenous thought as a decisive element. It was concluded that these principles entail an extensive list of duties for transnational companies concerning indigenous peoples, which must be implemented with consideration for indigenous worldviews - an underlying assumption for the application of indigenous rights. This list is not static; rather, it should evolve with human rights developments and ensure the ability to address new challenges arising from the relationship between transnational companies and indigenous peoples.